Flubendazole exhibits anti-glioblastoma effect by inhibiting STAT3 and promoting cell cycle arrest - Vítovcová, Barbora; Skarková, Veronika; Havelek, Radim; Soukup, Jiří; Pande, Ananya; Caltová, Kateřina; Rudolf, Emil (Scientific reports, 2023)
Glioblastoma multiforme (GBM) belongs to most aggressive and invasive primary brain tumor in adults whose prognosis and survival remains poor. Potential new treatment modalities include targeting the cytoskeleton. In our study, we demonstrated that repurposed drug flubendazole (FLU) significantly inhibits proliferation and survival of GBM cells. FLU exerted its effect by affecting microtubule structure and our results also suggest that FLU influences tubulins expression to a certain degree. Moreover, FLU effects decreased activation of STAT3 and also partially inhibited its expression, leading to upregulation of p53 signaling pathway and subsequent cell cycle arrest at G2/M phase as well as caspase-dependent cell death in GBM cells. These results suggest FLU as a promising agent to be used in GBM treatment and prompting further testing of its effects on GBM.
Keywords: dospělí; proliferace buněk; apoptóza; Cell Line, Tumor; Adult; Apoptosis; Cell Cycle; mebendazol; STAT3 Transcription Factor; Mebendazole; nádory mozku; lidé; Cell Cycle Checkpoints; kontrolní body buněčného cyklu; glioblastom; Glioblastoma; buněčný cyklus; transkripční faktor STAT3; Brain Neoplasms; Cell Proliferation; nádorové buněčné linie; Humans